Mathematical modeling of genome replication - Retkute, Renata; Nieduszynski, Conrad A.; Moura, Alessandro de (American Physical Society, 2012)
Eukaryotic DNA replication is initiated from multiple sites on the chromosome, but little is known about the global and local regulation of replication. We present a mathematical model for the spatial dynamics of DNA replication, which offers insight into the kinetics of replication in different types of organisms. Most biological experiments involve average quantities over large cell populations (typically >107 cells) and therefore can mask the cell-to-cell variability present in the system. Although the model is formulated in terms of a population of cells, using mathematical analysis we show that one can obtain signatures of stochasticity in individual cells from averaged quantities. This work generalizes the result by Retkute et al. [Phys. Rev. Lett. 107, 068103 (2011)] to a broader set of parameter regimes.